THE CORRELATION BETWEEN CLASSROOM ENVIRONMENT AND STUDENTS’ ENGLISH ACHIEVEMENT - Ady Irawan (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: This study was conducted to investigate Indonesian students’ perceptions toward classroom environment and their English achievement. This study attempted to reveal: (1) is there any significant correlation between physical classroom environment and students’ English achievement?, and (2) is there any significant correlation between psychosocial classroom environment and students’ English achievement. Based on the research problems above, the objectives of the study was to examine the correlation between classroom environment and students’ English achievement. The research design of this research was correlation research design. The sample was 34 sixth semester students of University of Islam Malang. The data analysis was using Pearson product moment. The result of correlation between students’ physical classroom environment and students English achievement showed that the p value is .034 that means there is significant correlation between classroom environment and students English achievement. For the psychosocial classroom environment, the result showed that p value is .780 that means there is no significant correlation between psychosocial classroom environment and students’ English achievement. In conclusion, the facilities in the classroom brings comfortable feeling to students’ in learning and affects students’ outcomes. Moreover, the relationship between students-students and teacher-students does not affect the students’ English achievement.keywords: Physical Classroom and Environment, Psychosocial